Le changement climatique et les propriétés du Conservatoire du littoral - Élodie Doze (VertigO)
Leading a land policy for a better protection of coastal areas and conservation of the ecological balances, the “Conservatoire du littoral” is faced, in its owner's quality, to the problem of coastal risks management, in link with climate change. This new challenge leads the question of the adaptation strategies to be implemented and of the place of the organization in the processes of dialogues with multi-stakeholders. Does the Conservatoire have to let evolve freely the seashore to increase naturalness? Does it have to participate to the public security, by accepting to maintain sea defence buildings on its lands? Do its priorities in term of acquisition have to be revised considering these new risks? Attentive to the considerations of safety and security, which worry the inhabitants of coastal zones and faithful to its founding principles, the Conservatoire does not adopt a dogmatic position today and prefers to adapt its strategies according to the territorial contexts. A prospective work on the modalities of long-term adaptation and on the evolution of the acquisition strategy was nevertheless initiated, with an objective: anticipate the possible scenarios, to face an uncertain future. Oscillating between present and future seashores, this article highlights a legal questioning on the articulation of responsibilities and missions of this atypical coastal stakeholder.